Interface Flow Limit Identification Using Focused Time Delay Network For MEPS Transmission - Norhafiz, Salim; Takao, Tsuji; Tsutomu, Oyama; Kenko, Uchida (Institute Of Electrical And Electronics Engineers Inc. (IEEE), 2016)
This paper investigates the use of use of Dynamic Neural Network (DNN) to extensively identify limitation of active power flow on the main transmission line for Malaysia Electric Power System (MEPS) network with PV generators provision. Conceptually, DNN is superior to Static Neural Network (SNN) in whatever errands are propounded from simple to complex systems. Compared to the conventional method using Continuous Power Flow (CPF) hereby with dynamical of neural network expedited identification of secure limitation on the network at given occasion. Namely, a Focused Time Delay Network (FTDN) which categorized as dynamic network model is developed in this study to specify the limit of active power flow over the network. Further, load variations e.g. low and high peak demand whilst considering N-1 criterion is deployed correspondingly. The simulations results are obtained using MATLAB software to identify MEPS network for inter area power transactions capability successfully presented and discussed thoroughly.